Tantra e hatha-yoga no Brasil: histórias de vida - Muniz, Concilia Cléria Ferreira (2021)
The aim of this doctoral dissertation is to analyze the relations between Tantra and Hatha-Yoga, its practices in Brazil and the life stories of Yoga teachers. From this perspective, we analyze the construction practices of what Flood (2006) calls “tantric body” in Tantra and Hatha-Yoga classes in Brazil, through a qualitative research of life stories recovery, conducted with teachers who established such practices in the country. In order to do so, we present the concept of Tantra in the Indian context; the purpose of getting to know the life stories of Tantra and Hatha-Yoga teachers in Brazil; we also investigate the construction practices of a “tantric body” in Tantra and Hatha-Yoga classes, on the basis of a Brazilian cultural context insertion, and then, through online observation, we identify the tantric elements included in Hatha-Yoga classes. Our research was guided by the hypothesis that the Yoga, taught as Hatha-Yoga in some schools of Brazil, contain tantric elements that are actually connected with the Indian tradition conceptions. This work is theoretically grounded on several authors, such as: Feuerstein (2006), Eliade (2010), Gnerre (2011), Zimmer (1986), Flood (2006) and Possebon (2006), who discuss the historical process of Yoga in Brazil and India, making a significant contribution to the area of Religious Studies. The data was collected by means of interviews. In such way, the oral life history was used as a methodological referential. We interviewed three teachers, two male and one female, aged between 64 and 80 years old. It is important to point out that two live in Rio de Janeiro and one lives in Paraíba. We discussed and presented the data in narrative form. In their speeches, the collaborators presented their experiences concerning the practices of Tantra and Hatha-Yoga in India and Brazil. The elements of the discussion were assembled in six main categories: the awakening of Yoga in the lives of Tantra and Hatha-Yoga teachers; perceiving Yoga and Tantra under multiple perspectives; understanding Tantra and Hatha-Yoga in Brazil; uncovering the construction of a “tantric body” in the Tantra and Hatha-Yoga classes; reinterpretation of Tantra and Hatha-Yoga in Brazil (originality); Yoga and rejuvenation: stories and experiences. As highlighted in the title of the work, two aspects were taken into account: the context that allowed the spreading of Tantra and Hatha-Yoga in Brazil and the life stories of those who collaborated and still collaborate so that these practices are more and more disseminated and experienced. Therefore, this study offers a reflection concerning the practices of Yoga in Brazil: there is a need for probing deeper into the Tantra-Yoga.